2016
DOI: 10.1080/10810730.2016.1153759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exergaming and Message Framing in School Environments on Physical Activity Attitudes and Intentions of Children and Adolescents

Abstract: Although interventions targeting the health of students in schools are becoming common, few studies have examined how health messages operate at the group level in school environments. This study examines the effects of message-based health interventions (extrinsic vs. intrinsic goal framing) in group environments (exergame competitive vs. exergame noncompetitive) on eliciting attitudes and intentions toward physical activity among children and adolescents. We conducted a 7-week school-based intervention progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Studies have shown that different media can have different impacts on adolescents’ attitude and online behavior (Chen, Ho, & Lwin, 2016; Ho, Poorisat, Neo, & Detenber, 2014; Lwin, Ho, Jung, Theng, Kim, & Wardoyo, in press). To control for the influence of attention to mass media and the Internet on the outcome variables, participants reported on a 7-point scale (1 = no attention at all and 7 = very close attention ) their attention to different content genres from various media channels.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that different media can have different impacts on adolescents’ attitude and online behavior (Chen, Ho, & Lwin, 2016; Ho, Poorisat, Neo, & Detenber, 2014; Lwin, Ho, Jung, Theng, Kim, & Wardoyo, in press). To control for the influence of attention to mass media and the Internet on the outcome variables, participants reported on a 7-point scale (1 = no attention at all and 7 = very close attention ) their attention to different content genres from various media channels.…”
Section: Methodsmentioning
confidence: 99%
“…Later, Lwin et al (2016) conducted another study on exergaming and PHM while focusing more on the difference in effects of physical activity beliefs between children and adolescence as well as intrinsic and extrinsic PHM from self-determination theory (SDT) perspective. The children showed significant improvement in combined effects of school group environment SDT-based health education messages on attitudes and intention while the adolescence did not.…”
Section: Integrated Theoretical Framework In a Physical Activity Intementioning
confidence: 99%
“…Open Access: e-Journal were only able to participate in the exergame once a week. In short, as exergames are a fusion of games and exercise, exergames may initially attract students to be more physically active because of the fun and enjoyment associated with the games in which over time, students may develop more positive attitudes toward exercise and exercise more (Lwin et al, 2016).…”
Section: Ijphcsmentioning
confidence: 99%
“…However, the 12-year-old children's attitudes improved to a lesser extent. Recently, Lwin et al(2016) studied the effect exergaming and health education messages have on attitudes towards PA of children and adolescents aged 8 to 17years, and indicated that the younger children were more positive when they participated in exergaming in comparison to the group who continued with normal PE lessons. The adolescents from junior high school showed no improvement in attitudes in either the competitive or non-competitive group (Lwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Lwin et al(2016) studied the effect exergaming and health education messages have on attitudes towards PA of children and adolescents aged 8 to 17years, and indicated that the younger children were more positive when they participated in exergaming in comparison to the group who continued with normal PE lessons. The adolescents from junior high school showed no improvement in attitudes in either the competitive or non-competitive group (Lwin et al, 2016). In South Africa, Uys et al(2016b) investigated what effect the Health Kick school-based intervention programme has on Grade 4 to Grade 6 learners, and found that the intervention programmes had no effect on children's fitness levels or attitudes; however, core strength and short-term PA participation increased.…”
Section: Introductionmentioning
confidence: 99%